APPROACH TO THE ASSESSMENT OF THE INDUSTRIAL ENTERPRISE SUSTAINABLE DEVELOPMENT - S. G. Svetun’Kov; V. P. Smol’Kin (Russian Journal of Economics and Law)
Objective: to determine and justify the integral indicator assessing socio-ecological-economic development of industrial enterprises. Methods: abstract-logical method. Results: basing on the assessment of social, environmental and economic subsystems, the technique is proposed to evaluate the enterprise sustainable development by a generalized (integral) indicator. The stages of forming the evaluation technique of social-ecological-economic development are described, taking into account international recommendations. The importance of each subsystem is proved. The threshold indicators of the integrated evaluation of sustainable development of the industrial enterprise are interpreted. Scientific novelty: the requirements are proposed to the formation of indicator systems of sustainable functioning and development of the enterprise. The indicators are divided into subsystems - social, environmental and economic. The system of indicators of sustainable development of the industrial enterprise is described. The formula for calculating the integral indicator is proposed. Practical value: the possibility to determine the place of the industrial enterprise in one of the three groups of integral evaluation. The information is necessary for government authorities to adjust the production structure, identify priority sectors and their additional investment and stimulate action. In addition, it will assist governments and other stakeholders to develop and implement such social-economic policy in the region that will allow to manage the region in the best way and thus ensure sustainable development, to improve well-being and quality of life of the population.